Meningkatkan Kemampuan Kognitif Melalui Media Gambar Pada Anak Kelompok B TK BA Aisyiyah Labuhan Haji - Mujahidah, Qotrin; Fahruddin; Baik Nilawati Astini; Baiq Nada Buahana (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research is motivated by cognitive abilities, particularly in the ability to recognize number symbols and count simple objects in children whose development has not yet reached its maximum, because kindergarten children are still unable to think abstractly and tend to think concretely. The purpose of this study is to improve children's cognitive abilities through the use of picture media in Group B kindergarten students. This research uses classroom action research (CAR), conducted in two collaborative cycles, starting from planning, implementation, observation, and reflection/evaluation. The data collection methods used were observation and documentation. Data analysis was carried out descriptively and qualitatively by examining the learning process and learning outcomes. The research subjects were 11 students of Group B at TK BA Aisyiyah Lobulian Haji. The results of the study showed that there was an improvement in the ability to recognize number symbols and count in children. In Cycle I, 11 children met the "starting to develop" (MB) criteria. In the implementation of learning using picture media, Cycle I obtained a total score of 37 with an average percentage of 43.7%, and improved in Cycle II with a total score of 57 with an average percentage of 89.6%. These results are considered successful because they exceeded the success indicator of 86%. Based on these findings, it can be concluded that using picture media can improve the ability to recognize number symbols and count in Group B children at TK BA Aisyiyah Labuhan Haji.